2014
DOI: 10.1002/2014tc003748
|View full text |Cite
|
Sign up to set email alerts
|

Terminal suturing of Gondwana along the southern margin of South China Craton: Evidence from detrital zircon U-Pb ages and Hf isotopes in Cambrian and Ordovician strata, Hainan Island

Abstract: Hainan Island, located near the southern end of mainland South China, consists of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 103 publications
(225 reference statements)
2
65
0
Order By: Relevance
“…Provenance and faunal data for early Paleozoic sandstones from the Sanya Block, suggest this region only became part of South China in the early to mid-Ordovician (Xu et al, 2014b). U-Pb ages and Hf isotope compositions of detrital…”
Section: Accepted Manuscript 15mentioning
confidence: 99%
See 2 more Smart Citations
“…Provenance and faunal data for early Paleozoic sandstones from the Sanya Block, suggest this region only became part of South China in the early to mid-Ordovician (Xu et al, 2014b). U-Pb ages and Hf isotope compositions of detrital…”
Section: Accepted Manuscript 15mentioning
confidence: 99%
“…A C C E P T E D M A N U S C R I P T (Xu et al, 2014b). The Qiongzhong Block remained part of the southeastern convergent plate margin of the South China Craton in the early Paleozoic.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Zhang et al (2014) proposed that the Nanhai terrane (including the Hainan massif) could be the missing link between South China and the Gondwana supercontinent, with the Zhenghe-Dapu fault as the suture zone between South China and the Nanhai terrane. Xu et al (2014b) suggested that Sanya Block on Hainan Island was separated from mainland South China (including the Qiongzhong Block, Hainan Island) until early to mid-Ordovician and that the juxtaposition of South China and West Australian cratons represented the final assembly of Gondwana. The previous researches have revealed the distinct tectonothermal events between Hainan Island and the South China.…”
Section: Position Of Hainan Island In Rodiniamentioning
confidence: 99%
“…The position of the Indochina Block in Gondwana has been of considerable controversy (Usuki et al, 2013). A number of studies suggest that Indochina Block was adjacent to the India-Australia margin of Gondwana, and most probably located close to north of India (Metcalfe, 1996(Metcalfe, , 2006Wang et al, 2010;Usuki et al, 2013;Xu et al, 2014). Torsvik and Cocks (2009) and Cawood et al (2013), however, plotted the Indochina Block as a discrete block in the paleo-Pacific, far away from the north margin of East Gondwana.…”
Section: Introductionmentioning
confidence: 99%